Textbook of violence assessment and management - Simon, Robert; Tardiff, Kenneth (Washington, DC ; London : American Psychiatric Publishing, 2008)
This is the first comprehensive textbook on assessing the potentially violent patient for mental health clinicians on the front lines of patient care. Six sections cover: Assessment Principles; Mental Disorders and Conditions; Treatment Settings; Special Populations - including children and adolescents and the elderly; Special Topics - including forensic issues, legal issues, sexual violence, violence toward mental health professionals, intimate partner violence, workplace violence, vehicular crashes, school violence, risk management of potentially violent patients.
Includes bibliographical references and index.
Keywords: Violence, prevention & control; Mental health services; Violence; Aggression; Social behaviour disorders; Risk assessment; Professional-patient relations